Οι "Κατηχήσεις" του Μιχαήλ Χωνιάτη. Χρονολόγηση και ιστορική προσέγγιση - ΜΑΥΡΟΜΜΑΤΗ, Καλλιόπη (Byzantina Symmeikta, 2010)
THE CATECHISMS OF MICHAEL CHONIATES. DATING AND HISTORICAL APPROACH The Catechisms of Michael Choniates, archbishop of Athens, are included in Spyridon Lampros’ Archive, who first studied the sources in 1906 and transcribed the texts from the manuscript Mosquensis Synodalis 218 (olim 230) and 219 (olim 262). Although he prepared a critical edition, he did not proceed with publishing. Eventually, his work has been digitized and the researcher can visit the Archive online through the website of the Laboratory of Digital Recording of the Public and Private Life of the Byzantines of the University of Athens (http://lamprosarcheio.arch.uoa.gr). The Catechisms are mainly, yet not exclusively, works of religious ethics; they also address the socioeconomic issues of the city of Athens at the end of the 12th century, and thus can be used as a supplementary source for this period. Indeed, the Catechisms offer a comprehensive account of the burdens endured by the Athenians, caused by the exploitative activities of state tax officers, usurers and pirates. On a different perspective, Choniates argues how adverse social conditions, such as poverty, immigration, and land tresspassing, modulate the social fabric and interpersonal relations. Although many of these issues are omitted or very briefly mentioned in other texts, they are clarified in the Catechisms.